UPAYA MENINGKATKAN HASIL BELAJAR PEMBELAJARAN TEMATIK DENGAN MENGGUNAKAN MEDIA KOMIK PADA SISWA KELAS III SD KARANGGONDANG KABUPATEN BANTUL TAHUN PELAJARAN 2013/2014 - Evi Puri Andari Anugrah Putri (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2014)
The purpose of this research is to improve learning outcomes through the use of thematic learning medium for students of class III comic Karanggondang Bantul elementary school year 2013/2014.This research is classroom action research ( CAR), which was commissioned jointly. Subjects in this study were students of class III SD Karanggondang Bantul totaling 34 students consisted of 17 female students and 17 male students. Object of this study is the result of the third grade elementary student learning Karanggondang Bantul on thematic learning using comics medium. Data collection techniques in this study was conducted with the test method and the method of observation. The instrument used in this study is testing and observation sheet. In this study, the test used is the test used. Test instrument is tested. Test trials tested are validity, distinguishing features, level of difficulty, and reliability. Data analysis techniques to determine the test with an average score on the learning outcomes of each cycle were used to determine the average value, the percentage increase in learning outcomes in each cycle, and the percentage of completeness that meet the KKM .The results showed that the learning outcomes on thematic learning using comics medium has increased from pratindakan, the first cycle and second cycle. This is indicated by an increase in the average value of student learning outcomes in pratindakan ie 65.56 increased to 73.09 in the first cycle and then again increased to 81.88 in the second cycle. The percentage of students who are able to reach KKM also increased each cycle is equal to 11.76% or 4 students at pratindakan, increased to 64.71%, or 22 people in the first cycle and the second cycle indicator of success has been achieved with the percentage of 82.35% or 28 students reached the KKM. Thus it is advisable for teachers to use comics in the thematic learning medium that can be considered as an alternative or efforts to improve student learning outcomes.Â